(untitled) (Research, Society and Development, 2025)
Introduction: Sarcopenia is a progressive and generalized musculoskeletal disorder, related to the reduction of muscle mass and functional capacity, in which gait speed is a means for assessing its severity. Objectives: To evaluate the gait speed of elderly sarcopenic patients and compare with results in the literature. Materials and methods: Study carried out at the orthopedics laboratory at Santa Casa de Alfenas and at the human performance laboratory at the physiotherapy clinic at the Federal University of Alfenas. Inclusion criteria: over 60 years old, SARC-F suggestive of sarcopenia and indicative handgrip test, without comorbidities. Sociodemographic, gait speed, and ethical procedures were evaluated. Results: 20 elderly people were selected, 30% obese, predominantly female; all had reduced gait speed. The sedentary, obese and with incomplete foundation presented lower gait speed. Discussion: The SARC-F questionnaire assesses the decline in muscle function, is easy to measure and mainly detects severe cases, with low sensitivity and high specificity. The handgrip test assesses muscle strength, indicating sarcopenia at values below the reference. Together, they indicate sarcopenia and are sufficient for intervention in clinical practice, however, the given study suggests the assessment of complementary gait speed, due to its easy measurement, ability to assess the physical performance of the elderly and predisposition to functional decline. Conclusion: All those included in the study demonstrated reduced gait efficiency. The groups with overweight, sedentary and incomplete fundamentals adopted a lower gait speed.